Cellulase Enzyme Production Using Actinobacillus sp. on Several Alternative Growth Media - Al-Arif , Mohammad Anam; Lamid, Mirni; Warsito, Sunaryo Hadi; Khairullah, Aswin Rafif; Hasib, Abdullah (Universitas Airlangga, 2024)
Cellulase enzymes are widely used in the food, beverage, animal feed, textile, and paper industries. The high cost of producing enzymes and low enzyme activity provides opportunities for using chemicals, and efforts are needed to produce cellulase enzymes economically through media optimization. This research aims to find alternative media that make it possible to produce cellulase enzymes with high activity. This research created a control media (M0) using pro-analysis chemicals and CMC as a carbon source. Three types of cellulolytic bacterial growth media were also created, consisting of technical chemicals, rice straw as a substrate, and different protein sources. M1: alternative media using urea as a protein source; M2: alternative media using powdered milk as a protein source; and M3: alternative media using chicken liver as a protein source. A total of 1% of cellulolytic bacteria (Actinobacillus sp.) was grown in each media and then incubated at 40°C for 33 hours at a speed of 140 rpm, and the production curve and cellulase enzyme activity were measured at every 3-hour interval. The results showed that the highest cellulase enzyme production was achieved at 24 hours using alternative media with powdered milk (M2) as a protein source. The cellulase enzyme activity produced was 2.9612 µ/ml.